Otto Neurath philosophy between science and politics - Cartwright, Nancy 1944- (Ideas in context, 1996)
An international team of four authors, led by distinguished philosopher of science, Nancy Cartwright, and leading scholar of the Vienna Circle, Thomas E. Uebel, have produced this lucid and elegant study of a much-neglected figure. The book, which depicts Neurath's science in the political, economic and intellectual milieu in which it was practised, is divided into three sections: Neurath's biographical background and the socio-political context of his economic ideas; the development of his theory of science; and his legacy as illustrated by his contemporaneous involvement in academic and political debates. Coinciding with the renewal of interest in logical positivism, this is a timely publication which will redress a current imbalance in the history and philosophy of science, as well as making a major contribution to our understanding of the intellectual life of Austro-Germany in the inter-war years